Effect of erosive pH cycling on different restorative materials and on enamel restored with these materials - Francisconi, L. F.; Honorio, H. M.; Rios, D.; Magalhaes, A. C. [UNESP]; Machado, M. A. A. M.; Buzalaf, M. A. R. (Operative Dentistry Inc, 2008)
This in vitro study evaluated the effect of erosive pH cycling on the percentage of surface micro-hardness change (%SMHC) and wear of different restorative materials and bovine enamel restored with these materials. Eighty enamel specimens were randomly divided into eight groups according to the restorative materials and immersion media used: GI/GV-resin-modifled glass-ionomer, GII/GVI-conventional glass-ionomer, GIII/GVII-resin composite and GIV/GVIII-amalgam. Over a period of seven days, groups GI to GIV were immersed in a cola drink (ERO) for 5 minutes, 3x/day and kept in artificial saliva between erosive cycles. Groups GV to GVIII were immersed in artificial saliva (SAL) throughout the entire experimental period (control). Data were tested for significant differences using ANOVA and Tukey's tests (p < 0.05). For %SMHC, considering the restorative materials, no significant differences were detected among the materials and immersion media. Mean wear was higher for the resin modified glass ionomer cement when compared to conventional cement, but those materials did not significantly differ from the others. For enamel analyses, erosive pH cycling promoted higher wear and %SMHC compared to saliva. There were no significant differences in wear and %SMHC of enamel around the different restorative materials, regardless of the distance from the restorative material (50, 150 or 300 mu m). In conclusion, there were only subtle differences among the materials, and these differences were not able to protect the surrounding enamel from erosion.